Systemic immune-inflammation index mediates the association between abdominal obesity and serum klotho levels - Chenchun Chen; Peng Tang; Wei Zhu (Scientific Reports)
Abstract The weight-adjusted waist index (WWI) has emerged as a reliable indicator of abdominal obesity. α-Klotho, a transmembrane protein, functions as a suppressor of aging. However, the relationship between these two factors remains underexplored. This study aims to investigate the association between WWI and serum α-Klotho levels in middle-aged and elderly Americans, with a focus on exploring the potential mediating role of the systemic immune inflammation index (SII). A cross-sectional study was conducted using data from 6997 middle-aged and elderly Americans participating in the National Health and Nutrition Examination Surveys (NHANES) between 2011 and 2016. Multiple linear regression analysis was employed to assess the relationship between WWI and serum α-Klotho concentrations. Additionally, mediation analysis was performed to investigate the mediating effect of SII on the relationships. Our analysis revealed a significant negative correlation between WWI and serum α-Klotho levels in the survey-weighted multiple linear regression models (adjusted percent change: -7.79; 95% CI: -10.15, -5.37). Mediation analysis demonstrated that the association between WWI and α-Klotho levels was partially mediated by SII (adjusted percent change: -0.88; 95% CI: -1.24, -0.45), with the proportion of mediation amounting to 11.6%. Further age-stratified results showed that the mediating role of SII was more pronounced among individuals aged ≥ 60 years, exhibiting a mediating effect of 26.3%, in contrast to 4.2% for those < 60 years. The findings suggest that WWI is inversely associated with serum α-Klotho concentrations and that this association is partially mediated by SII, especially in older people.